What is Media Assistance and (Why) Does it Matter? The Case of Polish Foreign Aid to the Media in Belarus and Ukraine - Aleksandra, Galus (Central European Journal of Communication, 2020)
The paper offers an analysis of media assistance, as a specific form of foreign aid, that Poland offers to strengthen media development in Belarus and Ukraine. It shows if Poland tailors media assistance according to the local context and existing challenges for democratic changes of recipient countries’ media systems. The study builds on the literature concerning the media, development and democratization, in particular looking at media assistance as both democratic aid and public diplomacy. It reveals that Poland’s approaches to media development in Belarus and Ukraine do differ: Poland mainly provides autocratic Belarus with technical support for media established outside of that country, while clearly focusing on media capacity development in democratizing Ukraine. The findings show that Polish media assistance, however, is unlikely to boost media freedom in Belarus as is usually expected as an outcome of democratic aid and is under-financed in the case of Ukraine.
Keywords: media assistance; media; poland; belarus; foreign aid; media development